IMPELEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KESADARAN SISWA MENGKONSUMSI MAKANAN DAN MINUMAN HALAL (Studi Kasus: SMPIT Titian Ilmu Kota Bekasi) - Putri Oktavianita B; Abdul Khoir HS (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
Islamic Religious Education is held with the intention of educating students to have noblecharacter and understanding. Prevent from consuming haram food and drinks. In this study, theformulation of the problem proposed 1) How is the implementation of Islamic Religious Educationlearning at SMPIT Titian Ilmu Bekasi?. 2) How do teachers increase students’ awareness in consumingfood and drinks at SMPIT Titian Ilmu Bekasi City? The purpose of this research is toTo find out fromthe research conducted is to find out the Implementation of Islamic Religious Education Learning onStudents’ Awareness in consuming food and drinks at SMPIT Titian Ilmu Bekasi City. This researchincludes qualitative descriptive research. To collect data, the author uses three methods, namely:(1). Interview method, the interview method is used to obtain data from students and teachers andprincipalsSMPIT Titian Ilmu(2). observation method, this method is used to see the conditions as ifand the condition of the canteenSMPIT Titian Ilmu(3). Documentary method, this method is used tofind out school documents, including school history, school area and school structure. Meanwhile, inanalyzing data, the author uses ”flow model analysis” from Miles and Huberman which includes threesteps, namely: data collection, data reduction, data presentation and drawing conclusions. The resultsof the study describe the implementation of Islamic Religious Education learning at SMPIT Titian IlmuBekasi, with the aim that the values, attitudes, and competencies produced are in accordance with theobjectives contained in the learning implementation design (RPP). In distance learning or (PJJ), PAIteachers provide the concept of learning with power points by displaying types of food and drinks thatare halal and have high nutritional content. It is intended that every student has a high awarenessto avoid foods and drinks that are not halal and have no benefits for the body. To increase students’awareness in consuming halal and good food and drinks, the teacher plays a very good role by usingthe right media.